Development and properties of dental Ti–Zr binary alloys. (December 2020) - Jiang, Jie; Zhou, Chuan; Zhao, Yanwei; He, Fuming; Wang, Xiaoxiang
Abstract: In this study, two medium Zr-containing Ti-based alloys with commercially pure titanium as control were systematically investigated to assess their potential biomedical application. After samples subjected to TMP and CR, it was found that the Zr addition significantly affected the microstructure, phase constitutions, mechanical properties and cytocompatibility. The microstructural results showed that increasing Zr concentrations resulted in more refined grains. Furthermore, Zr changed the phase constitution: CR Ti–20Zr was formed by the single α-phase while CR Ti–30Zr alloy was formed by the coexistence of α and deformation-induced FCC phases. The P-type FCC phase was dominant and more prone to occur than the B-type one. The mechanical tests demonstrated that the increasing Zr content led to a simultaneous increase in micro-hardness, strength and plasticity of CR samples due to the combined effects of solution strengthening, work hardening and the FCC phase. The SEM fractography indicated that the brittle fracture of CR Ti–20Zr due to deformation twins and ductile fracture of CR Ti–30Zr because of FCC phase. Furthermore, Ti–Zr alloys presented comparable cytocompatibility to the CP-Ti control based on cell viability, proliferation and intracellular O 2− content of MSCs. Specifically, alkaline phosphatase activity in BMSCs were significantly higher for grain refined CR Ti–30Zr. Considering all these results, CR Ti–30Zr alloy exhibited the optimal comprehensive performance to be potential dental materials. Graphical abstract: Image 1